Carnosol Induces ROS-Mediated Beclin1-Independent Autophagy and Apoptosis in Triple Negative Breast Cancer - Al Dhaheri, Yusra (Public Library of Science, 2014)
BACKGROUND: In this study we investigated the in vitro and in vivo anticancer effect of carnosol, a naturally occurring polyphenol, in triple negative breast cancer. RESULTS: We found that carnosol significantly inhibited the viability and colony growth induced G2 arrest in the triple negative MDA-MB-231. Blockade of the cell cycle was associated with increased p21/WAF1 expression and downregulation of p27. Interestingly, carnosol was found to induce beclin1-independent autophagy and apoptosis in MDA-MB-231 cells. The coexistence of both events, autophagy and apoptosis, was confirmed by electron micrography. Induction of autophagy was found to be an early event, detected within 3 h post-treatment, which subsequently led to apoptosis. Carnosol treatment also caused a dose-dependent increase in the levels of phosphorylated extracellular signal-regulated kinase 1 and 2 (pERK1/2). Moreover, we show that carnosol induced DNA damage, reduced the mitochondrial potential and triggered the activation of the intrinsic and extrinsic apoptotic pathway. Furthermore, we found that carnosol induced a dose-dependent generation of reactive oxygen species (ROS) and inhibition of ROS by tiron, a ROS scavenger, blocked the induction of autophagy and apoptosis and attenuated DNA damage. To our knowledge, this is the first report to identify the induction of autophagy by carnosol. CONCLUSION: In conclusion our findings provide strong evidence that carnosol may be an alternative therapeutic candidate against the aggressive form of breast cancer and hence deserves more exploration.